'Creating an Ecological Citizenship': Philosophical and Theological Perspectives on The Role of Contemporary Environmental Education. (30th October 2018) - Howles, Timothy; Reader, John; Hodson, Martin J.
Abstract : In its concern to evoke in its readership an appropriate response to the challenge posed by the contemporary environmental crisis, the recent papal encyclical Laudato Si': On Care for our Common Home differentiates between the task of human education, on the one hand, and the deeper and more abstract task of motivating the human will for change and action, on the other. What must take place, it asserts, is the creation of nothing less than an 'ecological citizenship'. To describe how this might be brought about, the encyclical employs the theological language of 'conversion'. However, the rationale for this suggestion, and the implications it would entail for the way in which educational programmes on the environment might be pursued, is developed only minimally in the encyclical itself. The objective of this article is to take up and develop this hint by offering some philosophical and theological perspectives on the idea of human motivation towards care for the environment, and by exploring the current state of affairs in environmental education in light of it. The article therefore aims to develop the encyclical's brief and unthematized suggestion regarding an 'ecological citizenship' in a practical and applied direction.© 2018 Trustees for Roman Catholic Purposes Registered